Common Turkic Ornithonyms in the Tatar and Tuvan Languages (Ethnolinguistic Aspect) - Safina, Elvira I. (The New Research of Tuva, 2025)
This article presents a comprehensive analysis of ornithonyms in the Tatar and Tuvan languages from the perspectives of lexical-semantic and linguocultural features, semantic flexibility of the lexical units denoting birds, and their potential to represent the traditional linguistic worldview. Tatar and Tuvan bird names are studied here for the first time in a comparative-contrastive, historical-semantic, and ethnolinguistic context. The research material comprises lexicographical and scientific sources, collections of folk literature, and the rich speech practices of both languages. The pathways of dissemination of Tatar and Tuvan ornithonyms into other related and unrelated languages are demonstrated; symbolic meanings of bird names are identified; folkloric traditions of using ornithological connotations and symbolism are examined. A detailed description is provided for Tatar and Tuvan bird names such as crane, raven (male), crow (female), eagle/golden eagle, falcon, hawk, and duck, as well as for the hyperonym “bird”. These ornithonyms are endowed with special ethnosemantic meanings among both Tatars and Tuvans. Ornithological images are reflected in the spiritual cultural heritage of Turkic peoples largely due to the ancestral sacralization of birds, perceived as connecting the higher world with the natural world.